The Implementation of Tri Dharma of Higher Education In Strengthening MSMEs Sector During The Covid-19 Pandemic - Nursita, Lisa; Idris, Ridwan (Universitas PGRI Semarang, 2024)
This study aims to investigate the contribution of the implementation of tri dharma of UIN Alauddin Makassar in the context of strengthening the MSMEs sector during the Covid-19 pandemic. The data analysis technique employed was a qualitative method using an analytical instrument of Likert scale, categorization with three criteria, tracing and analyzing documents of the implementation of researches and services carried out by UIN Alauddin Makassar. In this study, the sample was MSMEs in collaboration with UIN Alauddin Makassar. The research findings indicated that MSMEs were facing a decline in revenue and required support to adapt to the pandemic situations. Meanwhile, the form of empowering MSMEs through implementing research results and community services carried out by the academic communities of UIN Alauddin Makassar was still very few or in the adequate category. The implementation of tri dharma ended with the preparation of outputs, but the outcomes were still few. The implementation of the tri dharma of higher education, namely education, research, and community service, must develop MSMEs and be directed to be more responsive to the needs of contemporary society